Micromeria silicii, a new species from Croatia and its relationships with taxa of the M. microphylla group (Lamiaceae) - Bogdanović, Sandro; Ljubičić, Ivica; Sáez, Llorenç; Brullo, Salvatore (Phytotaxa, 2024)
Micromeria silicii, a new species from St. Andrea (Svetac) and Biševo Islands of Dalmatia (Croatia) is described and illustrated. Previously, it was attributed to M. microphylla, but careful morphological investigation allowed to differentiate it from the latter. In order to emphasize the relationships with the other taxa currentelly attributed to M. microphylla group were examined also M. acropolitana, M. cypria, M. carpatha, M. hispida, M. sphaciotica and M. rodriguezii, which are distributed in various territories of the Mediterranean area. All these species were studied from the taxonomical, nomenclatural and chorological point of view, as well as a new icononography was provided for some of them. Besides, an analitical key for all investigated species is given too.